(untitled) (Genius Repository, 2023)
Time management is the essence of success for any event. An event organizer’s ability to carefully plan and follow event routes is a criterion for having a good reputation in event management and in the world at large. However, the effectiveness of event management depends largely on the team’s ability to meet the client’s requirements, particularly in terms of time. The purpose of this research work is to determine the relationship between event management and time management. According to the researchers, in order for an organizer to be successful in the event industry, they must adhere to the time frame in completing the tasks during the event from the beginning to the end. In conclusion, most of the time, employees’ time management can affect their work efficiency because when the work is more than they can handle, there is not enough time to manage all their work. This article concludes with suggestions about the importance of time management in achieving high performance among event members, which reflects organizational effectiveness